2018
DOI: 10.1038/s41598-018-19544-2
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Mixing Fluoride and Chloride in Bioactive Silicate Glasses

Abstract: Adding fluoride into bioactive glasses leads to fluorapatite formation and a decrease in glass transition temperature. Recently, chloride has been introduced into glasses as an alternative to fluoride. The presence of the large chloride ion lowers glass crystallisation tendency and increases glass molar volume, which effectively facilitates glass degradation and bone-bonding apatite-like layer formation. However, there is no information regarding the effect of mixing fluoride and chloride on the glass structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…From EDS analysis, it was also possible to detect Cl on the BG‐2.5Co samples, and it may be originated from the Co precursor, cobalt chloride (CoCl 2 .4H 2 O). Chlorine ions may have been retained by the BG structure during the sol–gel process, coordinated with ions such as Ca 2+ , 46 but could also be related to unreacted cobalt chloride salt. However, further evaluation should be performed to confirm it, and it was not the goal of this work.…”
Section: Discussionmentioning
confidence: 99%
“…From EDS analysis, it was also possible to detect Cl on the BG‐2.5Co samples, and it may be originated from the Co precursor, cobalt chloride (CoCl 2 .4H 2 O). Chlorine ions may have been retained by the BG structure during the sol–gel process, coordinated with ions such as Ca 2+ , 46 but could also be related to unreacted cobalt chloride salt. However, further evaluation should be performed to confirm it, and it was not the goal of this work.…”
Section: Discussionmentioning
confidence: 99%
“…The new self-consistent core–shell force field parameters were used to investigate the atomic scale structure of the mixed halide CaO–SiO 2 –P 2 O 5 bioactive glasses (GPFCl2.6, GPFCl5.3, GPFCl12.2, and GPFCl23.6) as well as the structure of only fluoride-containing BGs (GPF3.0, GPF6.0, GPF13.6, GPF25.5) and only chloride-containing BGs (GPCl2.3, GPCl4.6, GPCl10.6, GPCl20.6) synthesized and experimentally characterized in the previous works by Chen et al whose compositions are reported in Table . Molecular dynamics simulations were carried out by using the DL_POLY package employing a well-established melt–quench computational protocol …”
Section: Computational Detailsmentioning
confidence: 99%
“…To exploit the potential of combining the benefits of both halogens into one composition, we have synthesized a series of mixed-fluoride/chloride-containing BGs . We observed that the properties of mixed bioactive glasses are influenced from the presence of both CaF 2 and CaCl 2 , which showed some similarities to those of the singly doped glasses.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In the last decades, considerable achievements have been made in using classical molecular dynamics simulations to predict glass structure and properties. [5][6][7][8] However, exploring the structure of boron-containing glasses through atomistic simulations has been historically a challenge due to the complexity of boron-oxygen bonding (which is not only partially covalent but also allows the boron coordination in glass to change with composition as shown in Equations [1] and [2]) and its dependence on the thermal history of glass. 9 Therefore, it has been difficult to develop adequate B-O interatomic potentials.…”
Section: Introductionmentioning
confidence: 99%